Characterization of a Novel Zinc Phosphate – Germanate Oxide System Doped with Erbium Ions. (2nd January 2019) - Bolunduţ, Liviu; Pop, Lidia; Păşcuţă, Petru; Culea, Eugen
Abstract: There is considerable interest in the discovery of new materials with applications in medicine. In this regard, a new germanium-zinc-phosphate oxide system with different contents of paramagnetic erbium ions was prepared and studied by X-ray diffraction and density and magnetic measurements. The structural and magnetic properties of the studied system were discussed as a function of the erbium ions content of samples. A crystalline ErPO4 phase appeared in the system for concentrations exceeding 3 mol% Er2 O3 . This structural change influences the density and Poisson's ratio values. The magnetic susceptibility measurements suggest that the studied samples obey the Curie law.